КОРРЕКЦИЯ УГЛЕВОДНОГО ОБМЕНА У БОЛЬНЫХ С МЕТАБОЛИЧЕСКИМ СИНДРОМОМ ПО ДАНЫМ СУТОЧНОГО МОНИТОРИРОВАНИЯ ГЛИКЕМИИ - А. М. Шилов; И. В. Еремина; А. Т. Абдуллаева (SINAPS LLC, 2012)
The article reviews mechanisms of insulin resistance, disorders of carbohydrate and lipid metabolism in patients with metabolic syndrome. Based on literature data and expert opinions of the World Health Organization the epidemiology and prognosis of the number of patients with diabetes mellitus (DM) type 2 in 2025 were presented. Based on the experience of examination and treatment of 75 patients with metabolic syndrome and impaired glucose metabolism from prediabetes to DM type 2 the predictive role of daily monitoring of glucose in the efficiency of the complex (Metformin, Tricor 145, Actovegin) in patients with this disease were shown.